2022
DOI: 10.31744/einstein_journal/2023ao0117
|View full text |Cite
|
Sign up to set email alerts
|

Immunophenotypic characterization of acute leukemias in Bahia, Brazil

Abstract: Santos et al. carried out a study on the immunophenotypic profile and demographic characteristics of a population of individuals diagnosed as new cases of acute leukemia over a period of 5 years. The main findings of the study were higher incidence of acute myeloid leukemia in women and CD66c and CD7 as the most frequent aberrant markers in acute lymphoblastic leukemia and acute myeloid leukemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 52 publications
0
1
0
1
Order By: Relevance
“…Overall, we observed the expression of CD13 in 21.8% of the B‐ALL patients, CD33 in 19.7% of the B‐ALL patients, and CD117 in 4.7% of the B‐ALL patients. The authors from high‐income and low‐income countries reported the aberrant expression of myeloid marker expression including 10.5%–54.5% CD13, 2.6%–89% CD33, and 0%–26.2% CD117 38,39,60,62–75 . These differences in frequencies of expression of various myeloid markers might be attributed to the inherent genetic differences among ethnic subpopulations, technical factors such as lack of uniformity in using monoclonal antibody clone type, and differences in flow cytometry methodology, processing, and data analysis 74,76 .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we observed the expression of CD13 in 21.8% of the B‐ALL patients, CD33 in 19.7% of the B‐ALL patients, and CD117 in 4.7% of the B‐ALL patients. The authors from high‐income and low‐income countries reported the aberrant expression of myeloid marker expression including 10.5%–54.5% CD13, 2.6%–89% CD33, and 0%–26.2% CD117 38,39,60,62–75 . These differences in frequencies of expression of various myeloid markers might be attributed to the inherent genetic differences among ethnic subpopulations, technical factors such as lack of uniformity in using monoclonal antibody clone type, and differences in flow cytometry methodology, processing, and data analysis 74,76 .…”
Section: Discussionmentioning
confidence: 99%
“…Posteriormente, um tremor de terra foi sentido, e desde então moradores dos bairros do Pinheiro, Bom Parto, Mutange e Bebedouro passaram a se defrontar com o surgimento danos estruturais nas ruas e imóveis. Visando esclarecer o fenômeno que acometia a região, um estudo geológico foi realizado e concluiu que o processo de afundamento do solo era decorrente as atividades de mineração para extração de sal-gema que vinha sendo realizada pela Braskem desde a década de 1970 (Ferreira;Bufrem, 2023;Nascimento;Sobrinho, 2022;Feitosa;Romeiro, 2023). No Brasil, a lei 14.750 de 2023 define desastre como a consequência de um incidente adverso, seja de natureza natural ou provocado por ação humana, que impacta negativamente ecossistemas e comunidades em situação de vulnerabilidade, resultando em danos substanciais tanto para a saúde humana quanto para os recursos materiais e o meio ambiente, acarretando prejuízos econômicos e sociais.…”
Section: Introductionunclassified